Brian Coles. (23rd September 2022) - Forbes, Neil; Payne‐Johnson, Catherine; Skerritt, Geoff
Abstract: Well known as an expert on avian medicine, his patients benefited from his interest and ingenuity, supported by meticulous recording of what worked and what didn't.